Investigations in GABAA receptor antibody-associated encephalitis. (14th March 2017) - Spatola, Marianna; Petit-Pedrol, Mar; Simabukuro, Mateus Mistieri; Armangue, Thaís; Castro, Fernanda J.; Barcelo Artigues, Maria I.; Julià Benique, Maria R.; Benson, Leslie; Gorman, Mark; Felipe, Ana; Caparó Oblitas, Ruben L.; Rosenfeld, Myrna R.; et al.
Abstract : Objective: To report the clinical features, comorbidities, receptor subunit targets, and outcome in patients with anti-GABAA receptor (GABAA R) encephalitis. Methods: Clinical study of 26 patients, including 17 new (April 2013–January 2016) and 9 previously reported patients. Antibodies to α1, β3, and γ2 subunits of the GABAA R were determined using reported techniques. Results: Patients' median age was 40.5 years (interquartile range 48.5 [13.75–62.35] years; the youngest 2.5 months old; 13 female). Symptoms included seizures (88%), alteration of cognition (67%), behavior (46%), consciousness (42%), or abnormal movements (35%). Comorbidities were identified in 11 (42%) patients, including 7 tumors (mostly thymomas), 2 herpesvirus encephalitis (herpes simplex virus 1, human herpesvirus 6; coexisting with NMDAR antibodies), and 2 myasthenia without thymoma. Brain MRI was abnormal in 23 (88%) patients, showing in 20 (77%) multifocal, asynchronous, cortical-subcortical T2/fluid-attenuated inversion recovery abnormalities predominantly involving temporal (95%) and frontal (65%) lobes, but also basal ganglia and other regions. Immunologic or tumor therapy resulted in substantial improvement in 18/21 (86%) assessable patients; the other 3 (14%) died (2 status epilepticus, 1 sepsis). Compared with adults, children were more likely to have generalized seizures ( p = 0.007) and movement disorders ( p = 0.01) and less likely to have a tumor ( p = 0.01). The main epitope targets were in the α1/β3 subunits of the GABAA R. Conclusions: Anti-GABAA R encephalitis is characterized by frequent seizures and distinctive multifocal cortical-subcortical MRI abnormalities that provide an important clue to the diagnosis. The frequency of symptoms and comorbidities differ between children (more viral-related) and adults (more tumor-related). The disorder is severe but most patients respond to treatment.